2018
DOI: 10.1038/s41598-018-24054-2
|View full text |Cite
|
Sign up to set email alerts
|

A death pheromone, oleic acid, triggers hygienic behavior in honey bees (Apis mellifera L.)

Abstract: Eusocial insects live in teeming societies with thousands of their kin. In this crowded environment, workers combat disease by removing or burying their dead or diseased nestmates. For honey bees, we found that hygienic brood-removal behavior is triggered by two odorants – β-ocimene and oleic acid – which are released from brood upon freeze-killing. β-ocimene is a co-opted pheromone that normally signals larval food-begging, whereas oleic acid is a conserved necromone across arthropod taxa. Interestingly, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 60 publications
3
54
1
1
Order By: Relevance
“…A large motile population, that can continuously acquire new territory, and that has a strategy to overcome stressful environments and survive mass extinction events promoted by the event itself, will also increase its chances of propagating beneficial mutations such as antibiotic resistance. We note that a response to cell death that benefits the living is not confined to bacteria, but is widespread in nature, as seen in insects (necromones) 63,64 , fishes 65 , birds 66 , and mammals 67 , possibly even in eukaryotic tumors 68 .…”
Section: Discussionmentioning
confidence: 99%
“…A large motile population, that can continuously acquire new territory, and that has a strategy to overcome stressful environments and survive mass extinction events promoted by the event itself, will also increase its chances of propagating beneficial mutations such as antibiotic resistance. We note that a response to cell death that benefits the living is not confined to bacteria, but is widespread in nature, as seen in insects (necromones) 63,64 , fishes 65 , birds 66 , and mammals 67 , possibly even in eukaryotic tumors 68 .…”
Section: Discussionmentioning
confidence: 99%
“…A large motile population, that can continuously acquire new territory, and has a strategy to overcome stressful environments and survive mass extinction events promoted by the event itself, will also increase its chances of propagating beneficial mutations such as antibiotic resistance. We note that a response to cell death that benefits the living is not confined to bacteria, but is widespread in nature, as seen in insects (necromones) 48,49 , fishes 50 , birds 51 , and mammals 52 , possibly even in eukaryotic tumors 53 .…”
Section: Discussionmentioning
confidence: 98%
“…After death, they rapidly peak in quantity to recruit undertakers in a timely manner and then gradually decrease. In the honeybee Apis mellifera , a volatile brood pheromone, β-ocimene, which signals food begging, continues to emit after death and recruits workers to uncap and remove dead larvae [ 23 ]. The above-mentioned examples represent three distinct patterns of using chemicals produced prior to death for the timely detection of death: diminished vital signs, increased early death cues and co-option of pheromones, respectively.…”
Section: Death Cues: the Novel And Conserved Chemical Signaturesmentioning
confidence: 99%
“…In a pioneering study of chemical stimuli for corpse disposal, Wilson et al [ 16 ] found that oleic acid was the most effective stimulus eliciting corpse removal in two ant species, Pogonomyrmex badius and Solenopsis saevissima . Since then, ‘fatty acid death cues’ have been found in many other social species, including the archaic ant Myrmecia vindex [ 39 ], the red ant Myrmica rubra [ 20 ], the fire ant Solenopsis invicta [ 40 ], a fungus-growing termite Pseudacanthotermes spiniger [ 41 ], two subterranean termites Reticulitermes virginicus [ 42 ] and R. flavipes [ 18 ], as well as the honeybee A. mellifera [ 23 ]. Oleic acid and linoleic acid are the most common stimuli for corpse disposal in those species; the two compounds have low volatilities and require direct contact or short distance detection.…”
Section: Death Cues: the Novel And Conserved Chemical Signaturesmentioning
confidence: 99%
See 1 more Smart Citation